Recommendations for data collection, analysis and reporting on anthropometric indicators in children under 5 years old (World Health Organization, 2019)
In 2016, the WHO-UNICEF Technical Expert Advisory Group on Nutrition Monitoring (TEAM) set up a working group (WG) to establish a set of recommendations for collecting anthropometric data that would improve data quality and standardize methods of analysis and reporting. Accurate anthropometric data are critical to provide reliable information to policy makers, programme managers, researchers and advocates, especially in the nutrition field. The quality of anthropometric data is also important in assessing how health and nutrition interventions are implemented and in guiding subsequent planning. This document is intended as a reference for the recommended steps in collecting, analyzing and reporting malnutrition estimates based on anthropometric data in nationally representative surveys. Its objective is to set out standardized methods for generating representative malnutrition estimates based on anthropometric data relating to weight, length/height and age in children less than 5 years old (or aged 0-59 months). Some recommendations included in this document are evidence-based while others rely more on practical experience and expert advice. When developing this technical guidance, it became clear that there is a need for further research to provide a wider range of evidence-based recommendations and to determine whether the use of technologically more advanced measuring instruments leads to the collection of more accurate data. The aim of this document is to guide survey implementers on how to improve the quality of anthropometric data for global monitoring. It should allow countries to track their progress towards the Global Nutrition Targets for 2025 and the SDGs for 2030 more effectively. Emergency settings are beyond the scope of this document. Some of its proposed recommendations and tools may be of use in emergencies but owing to the limited resources and pressing need for rapid assessments in such settings, some steps may not be feasible. A more context-bound approach may be necessary.